Microbial community analyses of produced waters from high‐temperature oil reservoirs reveal unexpected similarity between geographically distant oil reservoirs. Issue 4 (27th May 2018) - Kim, Daehyun D.; O'Farrell, Corynne; Toth, Courtney R. A.; Montoya, Oscar; Gieg, Lisa M.; Kwon, Tae‐Hyuk; Yoon, Sukhwan
Summary: As a preliminary investigation for the development of microbial‐enhanced oil recovery strategies for high‐temperature oil reservoirs ( 70 to 90°C), we have investigated the indigenous microbial community compositions of produced waters from five different high‐temperature oil reservoirs near Segno, Texas, U.S. ( 80 to 85°C) and Crossfield, Alberta, Canada ( 75°C). The DNA extracted from these low‐biomass‐produced water samples were analysed with MiSeq amplicon sequencing of partial 16S rRNA genes. These sequences were analysed along with additional sequence data sets available from existing databases. Despite the geographical distance and difference in the physicochemical properties, the microbial compositions of the Segno and Crossfield produced waters exhibited unexpectedly high similarity, as indicated by the results of beta diversity analyses. The major operational taxonomic units included acetoclastic and hydrogenotrophic methanogens ( Methanosaetaceae, Methanobacterium and Methanoculleus ), as well as bacteria belonging to the families Clostridiaceae and Thermotogaceae, which have been recognized to include thermophilic, thermotolerant, and/or spore‐forming subtaxa. The sequence data retrieved from the databases exhibited different clustering patterns, as the communities from close geographical locations invariably had low beta diversity and the physicochemical properties and conditions of the reservoirs apparently did not have a substantial role in shaping of microbial communities. Abstract : Indigenous microbial community compositions of produced waters of five different high‐temperature oil reservoirs in Segno, Texas and Crossfield, Alberta were examined as a preliminary investigation for development of microbial enhanced oil recovery strategies for high‐temperature oil reservoirs. The compositions of the sparse microbial population in Segno and Crossfield produced water samples exhibited unexpectedly high similarity despite the geographical distance and observed difference in the physicochemical make‐ups. This observation is unique among oil reservoir microbiomes, as the analyses of the microbial community compositions of previously sequenced produced water samples invariably exhibited clustering patterns according to the geographical proximity.